Sustainable Manufacturing: Effect of Material Selection and Design to the Environmental Impact in the Manufacturing Process - Mohd Hazwan Syafiq , Harun; Zahari, Taha; Hadi, Abdul Salaam (IOP Publishing, 2013)
The environmental impact of a manufacturing process is also dependent on the selection of the material and design of a product. This is because the manufacturing of a product is directly connected to the amount of carbon emitted in consuming the electrical energy for that manufacturing process. The difference in the general properties of materials such as strength, hardness and impact will have significant effect on the power consumption of the machine used to complete the product. In addition the environmental impact can also be reduced if the proposed designs use less material. In this study, an LCA tool called Eco-It is used. Evaluate the environmental impact caused by manufacturing simple jig. A simple jig with 4 parts was used as a case study. Two experiments were carried out. The first experiment was to study the environmental effects of different material, and the second experiment was to study the environmental impact of different design. The materials used for the jig are Aluminium and mild steel. The results showed a decrease in the rate of carbon emissions by 60% when Aluminium is use instead from mild steel, and a decrease of 26% when the-design is modified.